From Freedom From to Freedom To: New Perspectives on Intentional Action - Bonicalzi, Sofia; Haggard, Patrick (Frontiers in Psychology, 2019)
There are few concepts as relevant as that of intentional action in shaping our sense of self and the interaction with the environment. At the same time, few concepts are so elusive. Indeed, both conceptual and neuroscientific accounts of intentional agency have proven to be problematic. On the one hand, most conceptual views struggle in defining how agents can adequately exert control over their actions. On the other hand, neuroscience settles for definitions by exclusion whereby key features of human intentional actions, including goal-directness, remain underspecified. This paper reviews the existing literature and sketches how this gap might be filled. In particular, we defend a gradualist notion of intentional behaviour, which revolves around the following key features: autonomy, flexibility in the integration of causal vectors, and control.